Religious Orientation, Academic Stress and Religious Coping among First Year Undergraduate Students - Osman, Afaf; Ahmed, Iman Osman Mukhtar (IIUM Journal of Educational Studies, 2021)
The study aimed to assess the prevalence of religious orientation, academic stress, and the use religion as a means to cope with academic stress among first-year undergraduates. The sample consisted of 321 first year students from five faculties of a religiously oriented public university in Malaysia. The data were collected using three separated instruments: a Religious Coping Questionnaire, an Academic Stress Scale, and an Orientation Scale. Frequency analysis was used to examine the prevalence of stress, and religious orientation, while Pearson moment correlation was used to analyze the relationship among the three main constructs: religious coping, religious orientation and academic stress. The analysis ran an independent sample t-test to check for gender-differences in academic stress, religious coping and academic stress. The results showed high incidences of the religious orientation and religious coping among the sample of undergraduates, but no significant gender differences. The study substantiated that one of the means by which the first year students reduced their academic stress is through religious coping and religious orientation.